Pemahaman Spektrum Autisme: Tinjauan Psikopatologi Perkembangan, Deteksi Dini, dan Intervensi Integratif pada Anak Usia Dini - Yohana, Anggi Atma; Kurniawaty, Yulita (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Provide a comprehensive review of disorders within the autism spectrum, specifically autism and Asperger’s disorder, as forms of developmental psychopathology that emerge in early infancy. The autism spectrum is examined through the lens of definitions, behavioral characteristics, communication and social interaction deficits, as well as biological and intrapersonal etiologies. Individuals with autism demonstrate qualitative impairments in social relationships, symbolic communication, and behavioral flexibility, marked by restricted and repetitive interests and activities. Additionally, autism is strongly associated with neurobiological factors, including abnormalities in brain structures such as the amygdala and increased white matter volume, as well as complex genetic components. The study also emphasizes early detection through behavioral observation during the first year of life and highlights the importance of early developmental-based interventions, such as integrative models and the Lovaas behavioral modification program. The distinction between autism and Asperger’s disorder is addressed in terms of language development and cognitive functioning. These findings underscore the importance of interdisciplinary understanding in identifying and treating autism spectrum disorders and the necessity of holistic, individualized intervention approaches tailored to developmental profiles.